On the satire in Byzantium: ‘Ignorant’ or ‘Who claims to be a teacher ‘ by Theodorus Prodromos (Circe de clásicos y modernos, 2021)
It is offered here a Spanish translation of the Ἀμαθής, with introduction, notes and interpreting commentary; it is highlighted that this work represents the genre satura in Byzantium, according to a large tradition assumed by the ‘classicism’ of the XIIth century.
Keywords: Byzantium; satire; Prodromos; tradition; Ἀμαθής